1999
DOI: 10.1097/00125817-199903000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for trisomy 21: Maternal cigarette smoking and oral contraceptive use in a spopulation-based case-control study

Abstract: Our results indicate that categorizing cases of trisomy 21 by parent and timing of the meiotic error allows more precision in identifying risk factors and may shed light on mechanisms of meiotic nondisjunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 28 publications
1
82
2
3
Order By: Relevance
“…28 One recent report showed a positive association between maternal smoking and Down syndrome only for a subset of meiotically derived cases among young mothers. 29 Maternal smoking has also been associated with cardiac defects among infants with Down syndrome, 30 and Down syndrome could be better ascertained on the birth certificate when associated defects are present.…”
Section: Discussionmentioning
confidence: 99%
“…28 One recent report showed a positive association between maternal smoking and Down syndrome only for a subset of meiotically derived cases among young mothers. 29 Maternal smoking has also been associated with cardiac defects among infants with Down syndrome, 30 and Down syndrome could be better ascertained on the birth certificate when associated defects are present.…”
Section: Discussionmentioning
confidence: 99%
“…The set of environmental and behavioral risk factors to which women are exposed have also been implicated in the etiology of trisomy 21 birth (Chen et al 1999;Kaufman 1983;Padmanabhan et al 2004;Yang et al 1999;Martínez-Frías et al 2001). Moreover, recent epidemiological studies by our group (Ghosh et al 2011) on liveborn DS infants from Kolkata, India, revealed interactions among maternal age, recombination pattern of Ch21, and the mother's behavioral risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one risk factor for maternal non-disjunction has been definitive and well-established -maternal age [5][6][7]. An association has also been found between maternal smoking combined with oral contraceptives use and DS [8,9]. The primary prevention of the disease will be based on identification of genetic or environmental factors influencing maternal non-disjunction.…”
Section: Introductionmentioning
confidence: 99%